Designing ionophilic MXene-based organohydrogel electrolytes for high performance supercapacitor with wide-potential-window and anti-freezing properties - Moon, Juyoung; Lee, Juyun; Kang, Yun Chan; Kim, Jong Hak; Park, Jung Tae; Kim, Seon Joon (Pergamon Press Ltd., 2023)
Supercapacitors based on organohydrogel electrolytes can function at subzero temperatures and demonstrate a large potential range. However, for the development of next-generation energy-storage technologies, improvements in the ionic conductivity, mechanical strength, and flexibility of organohydrogel electrolytes are required. We employed Ti3C2Tx, an ionophilic MXene, as a nanofiller in this study to improve the ionic conductivity of organohydrogel electrolytes. Strong affinity for Li+ ions and good dispersibility in water/glycerol were obtained by the hydroxyl group's abundance on the surface of the ionophilic MXene. Due to the enhanced Li-ion hopping through the plentiful hydroxyl groups, an antifreezing supercapacitor based on the MXene/poly(vinyl alcohol) organohydrogel electrolyte (MXPVA-OHE) displayed a gravimetric capacitance as high as 19.84 F g-1 at room temperature and 3.49 F g-1 at -20 degrees C. Due to their high ionic conductivity, wide potential window, and favorable post-freezing recyclability, MXPVA-OHE-based supercapacitors are thus excellent energy-storage devices.